INTEGRASI DAN INTERKONEKSI AGAMA DAN POLITIK - Muhammad Nur (UIN Sunan Kalijaga Yogyakarta, 2017)
Discussion between religion and politic is never ending (read: Islam). Islam in fact was declare as last and perfect religion, cause of its universality and global character, which cover all of contemporary issues, as politic and government. Islamic historis had noted hundreds of book about this issues. Almost all of writing about Islam by moslem schoolar explain about it, over and above in modern era that can be devided in revivalist and modernist. This paper doesn’t analysis two trends, but prefer give argumentation for integration and interconnection about religion and politic in order to get appropriate understanding about it.